Exploring the Impact of Different Leadership Styles on Job Satisfaction among Primary School Teachers in the Achaia Region, Greece - Nick Panagopoulos; Kostas Karamanis; Sophia Anastasiou (MDPI AG, 2023)
This study explores the relationship between the transformational style of primary education Principals and the job satisfaction of their primary teachers in the Achaia region of Greece. A survey of primary school teachers in Greece (n = 411) revealed a strong positive association between transformational leadership and job satisfaction, highlighting the critical role of effective leadership in fostering a positive and supportive work environment for teachers. Pearson correlation analysis demonstrated significant correlations between leadership style and job satisfaction, considering both extrinsic and intrinsic parameters. Demographic factors, such as age and work experience, were associated with variations in satisfaction with the freedom to choose how to work, recognition for work, and promotion prospects. Specifically, older teachers expressed lower satisfaction levels in these areas. Moreover, the study highlighted the substantial impact of leadership style on job satisfaction. Age had a negative correlation with satisfaction with the freedom to choose how to work (r = −0.11, p = 0.019) and satisfaction with recognition for work (r = −0.112, p = 0.019), suggesting that older teachers tend to be less satisfied with these aspects of their jobs. Work experience had a negative correlation with satisfaction with promotion prospects (r = −0.14, p < 0.001), suggesting that more experienced teachers tend to be less satisfied with their prospects for career advancement. Transformational and personalized leadership styles were positively correlated with job satisfaction. Transformational leadership exhibited a strong positive correlation with satisfaction from the administration, colleagues, and working conditions (r = 0.785, p < 0.001). Transactional leadership also exhibits significant positive correlations with these aspects of job satisfaction, albeit to a slightly lesser extent. On the other hand, transactional leadership demonstrated a moderate positive correlation with overall job satisfaction (r = 0.301, p < 0.01), while no significant correlation is observed with satisfaction from the administration, colleagues, and working conditions. Passive laissez-faire leadership, in contrast, revealed negative correlations with all dimensions of job satisfaction, indicating a detrimental impact on the satisfaction levels of primary school teachers. These nuanced findings underscore the importance of considering multiple leadership styles in understanding their varied impacts on job satisfaction among teachers.